Non-enveloped virus inactivation potency of sodium dodecyl sulfate with citric and glutamic acids - Tan, Yong Wah; Bok, Chwee Fern; Lim, Brenda Jun Fang; Kong, Li Ying; Goo, Kian Sim; Ishida, Yoshiki; Liu, Jiquan; Chua, Chun Song; Chu, Justin Jang Hann (Frontiers in Microbiology, 2025)
Disinfection is one of the most important methods by which transmission of infectious diseases can be blocked, and efficacies differ depending on how they are used and the target organism. Small non-enveloped viruses are considerably less sensitive to disinfectants than enveloped viruses and vegetative bacteria or fungi and generally require strong protein-disrupting chemicals for effective inactivation, limiting their application in personal care products due to associated side effects. Sodium dodecyl sulfate (SDS) is a common anionic surfactant and relatively safe ingredient used in many personal care and hygiene products possessing protein-denaturing properties and has been reported to have antimicrobial efficacy against enveloped viruses and bacteria. With the aim of identifying milder disinfectants with broad-spectrum activity, including efficacy against non-enveloped viruses that are more difficult to inactivate, this study focused on evaluating the combinatorial efficacy of sodium dodecyl sulfate with organic acid (i.e., citric acid) and amino acid (i.e., glutamic acid) on feline calicivirus. Using an in vitro quantitative suspension test and electron microscopy, we have demonstrated the virucidal efficacy of SDS combinations with citric or glutamic acids on FCV. In addition, the spectrum of virucidal efficacy may potentially be extended to some human enteroviruses, and further research into their variable sensitivity to virus inactivation would be useful in developing these combinations into consumer products that target non-enveloped viruses.